Mind the Gaps: Intersex and (Re-productive) Spaces in Disability Studies and Bioethics - Holmes, M. Morgan (Journal of Bioethical Inquiry, 2008)
With a few notable exceptions disability studies has not taken account of intersexuality, and it is principally through the lenses of feminist and queer-theory oriented ethical discussions but not through ‘straight’ bioethics that modes valuing intersex difference have been proposed. Meanwhile, the medical presupposition that intersex characteristics are inherently disabling to social viability remains the taken-for-granted truth from which clinical practice proceeds. In this paper I argue against bioethical perspectives that justify extensive and invasive pre- and post-natal medical interference to eradicate intersex. I argue instead that to constitute the necessary conditions for the recognition of the intersexed child as a person, a life valid in its own right, clinicians must refrain from aggressive interference. Clinical specialists presuppose that intersexed children will be socially disabled and unrecognizable as persons; frustrated by the general failure of traditional interventions to assign a sex, clinicians are now pursuing prenatal technologies, including selective termination, to erase intersex.
Keywords: LGBTQIA2+; approches et analyses; biologie; bioéthique; corps; cours; discipline; identités LGBTQIA2+; intersexuation; lit4700; médecine; premier cycle; queer; sciences; soc2014; thématiques; éthique

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Number: 1
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales

L'astronomie au féminin - Nazé, Yaël (Vuilbert, 2008)
Qui a découvert un nombre exceptionnel de comètes et d’astéroïdes ? Une femme. Qui a permis d’organiser la population stellaire ? Des femmes. Et la loi permettant d’arpenter d’univers ? Encore et toujours… une femme ! Pourtant, quand il s’agit de citer au hasard un « astronome historique », on pense le plus souvent à des hommes : Galilée, Copernic, ou plus près de nous, Hubble. Certes, au cours des siècles, les femmes n’ont guère eu l’occasion d’accéder aux sciences en général et à l’astronomie en particulier. Est-ce pour autant une raison de croire en l’absence totale de leurs contributions ? À rebours des idées reçues, Yaël Nazé retrace le parcours de quelques scientifiques importantes qui ont en commun une particularité : leur sexe. L’ouvrage suit la trame des grandes découvertes, chaque domaine donnant lieu à une description des phénomènes astronomiques concernés et à un récit où l’on retrouve les grandes figures féminines de l’astronomie
Première publication : 2006
Keywords: astronomie; cours; discipline; fem1000; genre; histoire; histoire et politique; identités LGBTQIA2+; invisibilités; premier cycle; sciences; sciences humaines; thématiques

Medical photography: ethics, consent and the intersex patient - Creighton, S; Alderson, J; Brown, S; Minto, C L (BJU international, 2002)
In this review we discuss the effects that photography may have on the patient and present information obtained from our intersex services and research.
Keywords: LGBTQIA2+; corps; cours; discipline; gynécologie; identités LGBTQIA2+; lit4700; photographie médicale; premier cycle; ressource en ligne; sciences; thématiques; éthique

Experiments in knowing: Gender and method in the social sciences - Oakley, Ann (The New Press, 2000)
Ann Oakley came to widespread attention as part of the new school of British feminists to emerge in the 1960s, and has since earned a reputation as one of the most innovative feminist thinkers and social scientists writing today. In Experiments in Knowing, a major new work, Oakley integrates her personal and professional thinking to examine the historical development of methodology in the social and natural sciences, demonstrating how both fields have been subject to a process of "gendering." Oakley not only reconciles the long-standing opposition between the quantitative and the qualitative methods but shows that the experimental and intuitive approaches must be used in tandem to provide a full understanding of any subject of scientific inquiry. Written in accessible language, Experiments in Knowing addresses themes of common interest across such diverse fields as social policy, education, health, and women's studies. Certain to generate considerable debate, it is both a fascinating history of the practice of social science from a feminist perspective, as well as an argument for a new way of thinking about our ways of knowing.
Keywords: 1900-1999; approches et analyses; cours; discipline; europe; fem1000; genre; identités LGBTQIA2+; point de vue situé; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences; sciences humaines; sciences sociales; thématiques; théories féministes; épistémologie